The Differences Between Motor Attempt and Motor Imagery in Brain-Computer Interface Accuracy and Event-Related Desynchronization of Patients With Hemiplegia - Chen, Shugeng; Shu, Xiaokang; Wang, Hewei; Ding, Li; Fu, Jianghong; Jia, Jie (Frontiers in Neurorobotics, 2021)
Motor attempt and motor imagery are two common motor tasks used in brain-computer interface (BCI). They are widely researched for motor rehabilitation in hemiplegic patients. The differences between MA and MI tasks of hemiplegic patients can be used to promote BCI application. This study aimed to explore the BCI accuracy and event-related desynchronization (ERD) between the two tasks. We recruited 13 stroke patients and 3 traumatic brain injury patients, to perform MA and MI tasks in a self-control design. BCI accuracies from bilateral, ipsilesional and contralesional hemispheres were analyzed and compared between different tasks. Cortical activation patterns were evaluated with ERD and laterality index (LI). It showed that BCI accuracies of MA were significantly (p < 0.05) higher than MI in bilateral, ipsilesional and contralesional hemispheres in the alpha-beta (8-30 Hz) frequency band. There was no significant difference in ERD and LI between MA and MI tasks in 8-30 Hz frequency bands. However, in the MA task, there was a negative correlation between ERD values in channel CP1 and ipsilesional hemispheric BCI accuracies (r = -0.552, p = 0.041, n = 14) and a negative correlation between ERD values in channel CP2 and bilateral hemispheric BCI accuracies (r = -0.543, p = 0.045, n = 14). While in MI task, there were negative correlations between ERD values in channel C4 and bilateral hemispheric BCI accuracies (r = -0.582, p = 0.029, n = 14) as well as contralesional hemispheric BCI accuracies (r = -0.657, p = 0.011, n = 14). As for motor dysfunction, there was a significant positive correlation between ipsilesional BCI accuracies and FMA scores of hand part in 8-13 Hz (r = 0.565, p = 0.035, n = 14) in MA task and a significant positive correlation between ipsilesional BCI accuracies and FMA scores of hand part in 13-30 Hz (r = 0.558, p = 0.038, n = 14) in MI task. MA may achieve better BCI accuracy but similar cortical activations to MI task. Cortical activation (ERD) may have influence in BCI accuracy, which should be carefully considered in BCI motor rehabilitation of hemiplegic patients.